Effectiveness of Arterial Closure Devices for Preventing Complications With Percutaneous Coronary Intervention: An Instrumental Variable Analysis. (April 2016) - Wimmer, Neil J.; Secemsky, Eric A.; Mauri, Laura; Roe, Matthew T.; Saha-Chaudhuri, Paramita; Dai, David; McCabe, James M.; Resnic, Frederic S.; Gurm, Hitinder S.; Yeh, Robert W.
Abstract : Background—: Bleeding is associated with poor outcomes after percutaneous coronary intervention (PCI). Although arterial closure devices (ACDs) are widely used in clinical practice, whether they are effective in reducing bleeding complications during transfemoral PCI is uncertain. The objective of this study was to evaluate the effectiveness of ACDs for the prevention of vascular access site complications in patients undergoing transfemoral PCI using an instrumental variable approach. Methods and Results—: We performed a retrospective analysis of the CathPCI Registry from 2009 to 2013 at 1470 sites across the United States. Variation in the proportion of ACDs used by each individual physician operator was used as an instrumental variable to address potential confounding. A 2-stage instrumental variable analysis was used as the primary approach. The main outcome measure was vascular access site complications, and nonaccess site bleeding was used as a falsification end point (negative control) to evaluate for potential confounding. A total of 1 053 155 ACDs were used during 2 056 585 PCIs during the study period. The vascular access site complication rate was 1.5%. In the instrumental variable analysis, the use of ACDs was associated with a 0.40% absolute risk reduction in vascular access site complications (95% confidence interval, 0.31–0.42; number needed to treat=250). Absolute differences in nonaccess site bleeding were negligible (risk difference, 0.04%; 95% confidence interval, 0.01–0.07), suggesting acceptable control of confounding in the comparison. Conclusions—: ACDs are associated with a modest reduction in major bleeding after PCI. The number needed to treat with ACDs to prevent 1 major bleeding event is high.